Practical techniques for language teaching - Lewis, Michael; Hill, Jimmie (England: Language Teaching Publications, 1985)
This basic teacher training handbook for all less-experienced teachers covers the CTEFLA syllabus. The book is highly practical, theoretically sound and jargon-free, putting ELT in perspective for the new teacher. Areas covered include basic principles, classroom management and preparation
Keywords: English language -- Study and teaching -- Foreign speakers; English teachers -- Training of